KRITIK KUNTOWIJOYO TERHADAP ISLAMISASI ILMU - Fathony, Bimba Valid (Living Islam: Journal of Islamic Discourses, 2024)
As a form of response to the development of existing scientific paradigms, it is not uncommon for criticism to arise between each other. The development of the Islamization of science itself has given rise to criticism that the Islamization of science is only used as an instrument for the sterilization of modern science which is currently developing. So it has not yet emerged the true substance of Islam. In this research, researchers used qualitative research methods. This research is a type of library research, namely research whose object of study uses library data in the form of books, journals and articles as data sources. The results of the research entitled "Kuntowijoyo's Criticism of the Islamization of Science" explain, among other things, the Islamization of Science as a response to the crisis in modern society which is caused by the large amount of science that has developed based on the West. The Islamization of science is also understood as a way to liberate Western assumptions attached to Islamic science which are then replaced with an Islamic perspective. For Kuntowijoyo, science has a revolutionary nature. When Islam is made into a science, it will also become a paradigm, from which the ability to make changes will emerge. Kuntowijoyo tries to make this knowledge something objective, so objective knowledge does not need to be Islamized. He made a breakthrough, namely "Islamic science". The Islamization of Science makes Muslims closed to methods that originate from outside. Keyword: critics; Kuntowijoyo; Islamization of Science   Sebagai bentuk respon dari berkembangnya paradigma ilmu yang ada, maka tidak jarang muncul kritik antar satu sama lain. Berkembangnya Islamisasi ilmu sendiri telah memunculkan suatu kritikan dimana Islamisasi ilmu hanya dipakai sebagai instrument untuk sterilisasi terhadap ilmu modern yang tengah berkembang. Sehingga belum memunculkan substansi Islam yang sebenarnya. Pada penelitian ini peneliti menggunakan metode penelitan kulaitatif. Penelitian ini termasuk jenis penelitian pustaka (library research), yakni penelitian yang obyek kajiannya menggunakan data pustaka berupa buku-buku, jurnal, dan artikel sebagai sumber datanya. Hasil dari penelitian yang berjudul “Kritik Kuntowijoyo Terhadap Islamisasi Ilmu” ini dijelaskan antaranya, Islamisasi Ilmu sebagai bentuk respon terhadap krisis di masyarakat modern yang diakibatkan karena banyaknya ilmu yang berkembang bertumpu pada Barat. Islamisasi Ilmu juga dipahami sebagai cara untuk membebaskan asumsi-asumsi Barat yang melekat pada ilmu pengetahuan Islam yang selanjutnya diganti dengan cara pandang Islam. Bagi Kuntowijoyo ilmu memiliki sifat revolusioner. Saat Islam dijadikan ilmu maka ia akan sekaligus menjadi paradigma dari situ akan timbul suatu kemampuan untuk membuat perubahan. Kuntowijoyo berusaha menjadikan ilmu tersebut sebagai sesuatu yang objektif, maka pengetahuan yang objektif tidak perlu diislamisasi. Ia membuat suatu terobosan yaitu “pengilmuan Islam”. Islamisasi Ilmu menjadikan umat Islam tertutup dengan metode-metode yang bersumber dari luar. Kata kunci: kritik; Kuntowijoyo; Islamisasi Ilmu